Hyaline-vascular variant of angiofollicular lymph node hyperplasia with systemic manifestations and response to corticosteroids. Issue 9 (September 1983) - Summerfield, G P; Taylor, W; Bellingham, A J; Goldsmith, H J
Abstract : We report two cases of angiofollicular lymph node hyperplasia of the hyaline-vascular type. The patients were atypical in having systemic complications, which are much more commonly seen in the plasma cell variant of this disorder. In each case, the diagnosis was established some years after the initial presentation. Both patients presented with unusual systemic manifestations. The exact mechanism underlying the associated features is unknown, but these cases provide some evidence that the disease is primarily a vascular proliferative or inflammatory disorder. All manifestations of the disease responded to the administration of prednisolone with rapid reduction of dosage to less than 10 mg daily. Maintenance therapy may be required to prevent relapse.